Strategi Pemasaran Kepala Sekolah untuk Meningkatkan Mutu Pendidikan di SD Nation Star Academy Surabaya: Principal's Marketing Strategy to Improve the Quality of Education at SD Nation Star Academy Surabaya - Nur Ali; Erny Roesminigsih; Yatim Riyanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
One of the efforts to achieve sustainable competitive advantage is through marketing strategy, both for companies that produce goods and services and for educational institutions. Marketing strategy in education can be considered in designing overall program planning to meet the satisfaction of stakeholders and the community of educational service users. This study aims to determine, explain, and analyze marketing strategy and implementation of marketing strategy to improve school quality at SD Nation Star Academy Surabaya. The research method uses a qualitative approach. Data collection was carried out through interviews, observations, documentation, and the application of triangulation techniques. Data analysis involves the process of data reduction, presentation, and verification. The results of this study reveal that (1) the form of educational marketing strategy, especially marketing strategy, has been carried out effectively through understanding the needs of consumers who utilize educational services, and (2) the implementation of educational marketing strategy at SD Nation Star Academy Surabaya on each marketing mix indicator has been running well, although there are still some weaknesses found. Strong cooperation among stakeholders, including the principal, staff, teachers, and students, who all fulfil their responsibilities with a common goal of improving the quality of education.